Extreme Flooding and Nitrogen Dynamics of a Blackwater River. Issue 12 (10th December 2021) - Neville, J. A.; Emanuel, R. E.; Nichols, E. G.; Vose, J.
Abstract: Extreme floods, including those expected to become more frequent in a warming world, may impact nutrient metabolism in streams. However, flood impacts on spatial and temporal variability of nutrient dynamics on large rivers (e.g., fourth order and higher) have been understudied. In 2016, Hurricane Matthew provided a unique opportunity to evaluate nitrate retention and processing on the Lumbee River, a blackwater stream in southeastern North Carolina. The 3, 000+ km 2 watershed received as much as 400 mm of rain in 48 hr as the storm moved across the Atlantic Coastal Plain. Resulting floods in the watershed were the largest on record, based on more than 80 years of continuous streamflow measurements at the watershed outlet. We used a modified Lagrangian sampling method to collect water samples and supporting water quality data at multiple points along three reaches of the Lumbee River for several months before and after Hurricane Matthew. Samples were analyzed for nitrate‐nitrogen and used to estimate retention and areal uptake rates for multiple subsections within each reach. Although nitrate‐nitrogen concentrations did not change significantly after the flood, we found that the spatial variability of within‐reach retention and areal uptake increased substantially following the flood, evidenced by changes to within‐reach interquartile ranges. The spatial variability of areal uptake returned to pre‐flood levels approximately eight months after Hurricane Matthew, but retention variability remained elevated at the end of our field study. These results highlight the potential for extreme flooding to impact biogeochemical processes in large rivers long after flood waters subside. Plain Language Summary: Large floods, such as those following tropical storms, can radically change streambeds and aquatic environments. These changes can have consequences for nutrient processing in streams. Little is known about the impacts of extreme floods in large rivers, particularly with respect to the longevity of their effects on nutrient processing. In 2016, Hurricane Matthew brought widespread flooding to the Lumbee River watershed, located in southeastern North Carolina. We sampled nitrate‐nitrogen along three reaches of the river before and after flooding and were able to compare nitrate processing before and after to determine if large floods could have lasting influences on these characteristics. Significant differences in percent removal and removal rates before and after flooding were found at only one reach, but we did observe a substantial increase in the variability of nitrogen processing in all three reaches. These results shed new light on nitrogen processing in large rivers by identifying potentially important biogeochemical changes caused by extreme flooding. Key Points: Spatial variability of Nitrate ‐N retention and areal uptake increased in the months after extreme flooding on a blackwater river Eight months post flood impacts to nitrate‐N areal uptake could not be detected, but increased spatial variability of retention remained Results suggest some level of resiliency to flood disturbance within larger rivers